A solid waste-based high-toughness geopolymer for 3D printing and preparation method thereof

By using solid waste-based high-tough polymers, combining pretreatment fibers and using ground polymer composite dry mix, the problems of insufficient toughness and complex construction process of 3D printed ground polymers are solved, and the effects of high toughness and simplified construction are achieved.

CN116283099BActive Publication Date: 2025-04-29TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310277913.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-21
Publication Date
2025-04-29
Estimated Expiration
2043-03-21

AI Technical Summary

Technical Problem

The existing 3D printed polymers have shortcomings in toughness and are complex in construction processes, making it difficult to meet the needs of large-scale on-site construction.

Method used

The construction process is simplified by pretreatment of the fiber and composite dry mix of polymers using solid waste, which consists of aluminosilicate precursor materials, composite solid exciters, thixotropic agents, fine aggregates, fibers and water.

Benefits of technology

It improves the toughness of the 3D printed polymer, simplifies the construction process, reduces construction difficulty, improves production efficiency, and is suitable for large-scale on-site construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116283099B_ABST
    Figure CN116283099B_ABST
Patent Text Reader

Abstract

The present invention relates to a solid waste-based high-toughness geopolymer for 3D printing and a preparation method thereof, wherein the components of the geopolymer are respectively 100 parts of aluminosilicate precursor material, 13.5-16.5 parts of composite solid activator, 1.0-4.0 parts of thixotropic agent, 120-140 parts of fine aggregate, 0.60-1.20 parts of fiber and 36-44 parts of water in mass parts; the method is specifically: soaking the fiber in a dispersion liquid; mixing and stirring to obtain a geopolymer composite dry blend; mixing and stirring the geopolymer composite dry blend and water to obtain a geopolymer slurry; 3D printing the geopolymer slurry to obtain a 3D printed geopolymer entity. Compared with the prior art, the present invention overcomes the poor toughness of a two-component geopolymer and the difficulties in transporting, storing and mixing a strong alkaline liquid activator, and solves the problem of weakening the rheological properties of the slurry caused by the incorporation of geopolymer fibers, thereby causing the deterioration of printability in 3D printing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid waste resource utilization and 3D printing building materials, and relates to a solid waste-based high-toughness geopolymer for 3D printing and a preparation method thereof. Background Art

[0002] Since the beginning of the 21st century, with the strategic development of the fourth industrial revolution (Industry 4.0), additive manufacturing technology based on intelligence and automation has developed rapidly. Among them, 3D printing technology based on layer-by-layer stacking molding process has achieved significant success in the construction industry and has been regarded as a future technology that changes the traditional construction model. The advantages of construction 3D printing technology lie in the lower maintenance, operation, labor and construction time costs. If the construction 3D printing technology is fully implemented, it will significantly reduce the resource and energy consumption of the construction industry, thereby reducing capital costs and labor demand. It is estimated that the use of construction 3D printing technology can reduce 30-60% of construction material consumption and 50-80% of labor costs, while shortening the construction period by 20-30%.

[0003] At present, geopolymers prepared by treating solid waste using alkali-activated cementitious materials technology are considered to be green and low-carbon cementitious materials with great sustainable potential. At present, solid wastes commonly used to prepare geopolymers include fly ash, mineral powder, red mud, etc. Fly ash is a solid waste derived from the production process of thermal power plants, metallurgy, chemical industry and other industries. The incombustibles in coal are partially melted due to high temperature, and a part of the molten fine particles are quenched and solidified in a vitreous state. These vitreous bodies have high potential chemical reaction activity and are separated and collected by dust collectors, which is fly ash. According to statistics, fly ash accounts for about 15% of the mass of raw coal, and its output in 2020 is as high as 650 million tons. Granulated blast furnace slag powder (referred to as mineral powder) is a molten material with silicates and aluminosilicates as the main components derived from the smelting of pig iron in a blast furnace. It is quenched into a loose, porous granular glassy material. At its peak in 2013, the annual production of mineral powder reached 126 million tons; currently, the annual production of mineral powder is 90 million tons. According to cement plant reports, each ton of cement produced emits about 0.81-0.91 tons of carbon dioxide. If fly ash and mineral powder are used as precursor materials and other materials are used to prepare geopolymers, it is estimated that each ton of geopolymer emits 0.18-0.67 tons of carbon dioxide. Therefore, the development of solid waste-based high-toughness geopolymers provides a feasible solution for the sustainable green development of the building materials industry.

[0004] At present, geopolymers are mostly prepared from a two-component mixture of a liquid alkali activator (single or mixed solution such as sodium silicate, sodium hydroxide and water glass) and a precursor material (such as fly ash, mineral powder, and metakaolin). Compared with traditional cement-based materials, two-component geopolymers have advantages such as good cohesion, early strength and fast hardening; however, the transportation, storage and mixing of strong alkaline solutions and the high viscosity of two-component geopolymers have brought new challenges to large-scale 3D printing.

[0005] Geopolymer materials have poor toughness and are prone to brittle fracture. Introducing fiber components into the geopolymer system can improve the flexural strength and toughness of the geopolymer matrix and increase its service life. Currently, the types of fibers commonly used in cast geopolymers include carbon fiber, basalt fiber, steel fiber, polymer fiber, glass fiber and natural fiber. However, when fiber components are introduced into the 3D printing geopolymer system, the buildability of the geopolymer slurry does not change significantly; but its rheological properties are significantly weakened, and its pumpability and extrudability deteriorate rapidly with the increase in fiber content, and its interlayer bonding strength is slightly reduced. Therefore, an appropriate pretreatment process should be used to reduce the weakening of 3D printability by fibers.

[0006] Patent CN113998929A discloses a high-performance geopolymer concrete and its preparation method. The geopolymer concrete includes the following raw materials by mass: 1550-1600 parts of mineral powder, 155-165 parts of silica fume, 250-270 parts of fly ash, 500-1200 parts of fine aggregate, 200-800 parts of ceramic ball aggregate, 867-892 parts of activator, 78-234 parts of fiber, 20-24 parts of water reducer, and 0-109 parts of water. Although the patent prepares a geopolymer with ultra-high compressive strength by introducing fiber and ceramic ball aggregate components, the preparation process is relatively cumbersome and does not meet the requirements of architectural 3D printing for rheological properties, and is not suitable for actual architectural 3D printing engineering applications.

[0007] Patent CN113277791A discloses an industrial solid waste geopolymer material for building 3D printing and a preparation method thereof. The industrial solid waste geopolymer material for building 3D printing includes 0.1-50 parts of slag, 0.1-40 parts of steel slag, 0.1-30 parts of silica fume, 0.1-30 parts of fly ash, 0.1-10 parts of alkali activator, 0.1-2.0 parts of water reducer, 0.1-2.5 parts of thixotropic agent, 0.1-1.0 parts of thickening and water-retaining agent, 0.01-0.2 parts of defoaming agent and 0.1-2.0 parts of fiber. Although this patent uses a variety of industrial solid waste to prepare 3D printing geopolymers, it effectively improves the utilization rate of solid waste. However, the precursor material used has poor stability, no aggregate is added, and the comprehensive utilization rate of resources is low; at the same time, its construction process is complicated, the open time is less than 20 minutes, and it is not feasible for large-scale on-site construction. Summary of the invention

[0008] The purpose of the present invention is to overcome at least one defect in the above-mentioned prior art and to provide a solid waste-based high-toughness geopolymer for 3D printing and a preparation method thereof. The 3D printing geopolymer of the present invention has high toughness and a simple preparation process.

[0009] The purpose of the present invention can be achieved by the following technical solutions:

[0010] One of the technical solutions of the present invention is to provide a solid waste-based high-toughness geopolymer for 3D printing, wherein the components of the geopolymer are, by mass, 100 parts of aluminosilicate precursor material, 13.5-16.5 parts of a composite solid activator, 1.0-4.0 parts of a thixotropic agent, 120-140 parts of fine aggregate, 0.60-1.20 parts of fiber and 36-44 parts of water.

[0011] The mixture prepared by adding water and mixing it in a specified proportion at the construction site is called a single-component geopolymer. The geopolymer composite dry mix is ​​easy to transport, and there is no need to consider anti-corrosion and anti-freezing issues. It can be directly added with water and stirred on site, which significantly reduces the difficulty of construction and effectively improves production efficiency. Therefore, the single-component geopolymer prepared from the geopolymer composite dry mix has advantages in transportation, storage and on-site construction.

[0012] Furthermore, the aluminosilicate precursor material includes fly ash, mineral powder, light bentonite and light calcium carbonate, and the components are 70-80 parts by mass of fly ash, 10-25 parts of mineral powder, 2.0-5.0 parts of light bentonite and 2.0-5.0 parts of light calcium carbonate.

[0013] Furthermore, the composite solid activator comprises anhydrous sodium silicate and sodium silicate nonahydrate, and the components are 2.5-5.0 parts of anhydrous sodium silicate and 8.5-12.0 parts of sodium silicate nonahydrate in terms of mass fraction.

[0014] Furthermore, the thixotropic agent is a nano-magnesium aluminum silicate (Nano-Magnesium Aluminium Silicate) plastic thickener.

[0015] Furthermore, the fine aggregate is formed by mixing 20-40 mesh and 40-80 mesh quartz sand in a mass ratio of 1:(1-2).

[0016] Furthermore, the fiber is polypropylene fiber (PP) or polyvinyl alcohol fiber (PVA), with a length of 6.0-9.0 mm, a diameter of 18-48 μm, and a specific gravity of 0.91-0.97.

[0017] One of the technical solutions of the present invention is to provide a method for preparing a solid waste-based high-toughness geopolymer for 3D printing, the method comprising the following steps:

[0018] (1) Soak the fiber in the dispersion and then take it out to air dry;

[0019] (2) fully mixing and stirring the aluminosilicate precursor material, the composite solid activator, the thixotropic agent, the fine aggregate and the fiber with a high-speed dry powder mixer to obtain a geopolymer composite dry blend;

[0020] (3) mixing the geopolymer composite dry mix and water in a concrete mixer to obtain a geopolymer slurry with good fluidity and stacking properties;

[0021] (4) placing the geopolymer slurry in a printing bin of a frame-type concrete 3D printer, adjusting the extrusion rate of the printing nozzle and the horizontal / vertical stepping speed according to a preset shape and printing path, thereby obtaining a 3D printed geopolymer entity (or component) of a specific configuration;

[0022] (5) 24-48 hours after printing is completed, the 3D printed geopolymer entity has basic plastic strength and can be transferred to the curing room for curing to the specified age.

[0023] As a preferred technical solution, after the 3D printed geopolymer entity is printed, it is necessary to spray an appropriate amount of water on the outer surface using a spray bottle every 4-12 hours (depending on the air humidity and ventilation conditions) to maintain the humidity balance inside and outside the specimen to prevent shrinkage and cracking.

[0024] Furthermore, in step (1), the solute of the dispersion is a ZY-DP type nanomaterial dispersant, and the solvent is water, 75% ethanol or anhydrous ethanol, with a mass fraction of 0.5-5.0%.

[0025] Furthermore, the soaking time in step (1) is 24-48 hours.

[0026] Furthermore, the mixing and stirring time in step (2) is 10-20 minutes, and the mixing and stirring time in step (3) is 5-10 minutes.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] (1) The raw materials of the present invention are composed of only two components: geopolymer composite dry mix and water. The geopolymer composite dry mix has the advantages of being simple and convenient in preparation, transportation, storage and on-site construction, and is in line with the traditional concrete mixing production process to the greatest extent;

[0029] (2) The green building materials prepared by the present invention using various solid wastes can effectively improve the production environment and improve production quality; the materials can be recycled or reused to reduce resource and environmental loads;

[0030] (3) The present invention pre-treats the fibers with a dispersion solution, which can effectively alleviate the negative effects of the fibers on the printability of the geopolymer slurry and improve the toughness of the 3D printed geopolymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a flow chart for preparing a solid waste-based high-toughness geopolymer for 3D printing in an embodiment of the present invention;

[0032] Figure 2 This is a schematic diagram of sampling of a 3D printed solid waste-based high-toughness geopolymer entity in an embodiment of the present invention;

[0033] Figure 3 This is a schematic diagram of loading stress for the XY plane compressive strength test of a 3D printed solid waste-based high-toughness geopolymer specimen in an embodiment of the present invention;

[0034] Figure 4 Schematic diagram of the loading stress of the YZ plane compressive strength test of the 3D printed solid waste-based high-toughness geopolymer specimen in the embodiment of the present invention;

[0035] Figure 5 Schematic diagram of loading stress for XY plane flexural strength test of 3D printed solid waste-based high-toughness geopolymer specimens in an embodiment of the present invention;

[0036] Figure 6 Schematic diagram of loading stress for the YZ plane flexural strength test of the 3D printed solid waste-based high-toughness geopolymer specimen in an embodiment of the present invention. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.

[0039] The embodiment uses F class 2 fly ash, S95 grade mineral powder, 1250 mesh light bentonite and light calcium carbonate; the modulus of anhydrous sodium silicate is 1.4, and the modulus of nonahydrate sodium silicate is 1.0; the fine aggregate is a mixture of 40 mesh and 80 mesh quartz sand in a mass ratio of 1:2; the polypropylene fiber (Polypropylene fiber, PP) has a length of 6.0 mm, a diameter of 18 μm, and a specific gravity of 0.91; the thixotropic agent uses the American VEEGUM ULTRA type plastic thickener, the main chemical component of which is nano-magnesium aluminum silicate (Nano-Magnesium Aluminium Silicate); the dispersant uses the ZY-DP type nano material dispersant produced by Zhongyan Technology Co., Ltd.

[0040] Embodiment 1:

[0041] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent, and 42 parts of water.

[0042] Embodiment 2:

[0043] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 70 parts of fly ash, 20 parts of mineral powder, 5.0 parts of light bentonite and 5.0 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 44 parts of water.

[0044] Embodiment 3:

[0045] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 12.0 parts of sodium silicate nonahydrate, 2.5 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 40 parts of water.

[0046] Embodiment 4:

[0047] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 140 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 43 parts of water.

[0048] Embodiment 5:

[0049] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.60 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0050] Embodiment 6:

[0051] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 1.00 part of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0052] Embodiment 7:

[0053] A solid waste-based high-toughness geopolymer for 3D printing, wherein the raw materials are respectively, by mass, 70 parts of fly ash, 20 parts of mineral powder, 5.0 parts of light bentonite and 5.0 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 1.0 parts of thixotropic agent and 44 parts of water.

[0054] Comparative Example 1:

[0055] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that lightweight bentonite and lightweight calcium carbonate are removed and replaced with fly ash and mineral powder.

[0056] The raw materials are respectively as follows in parts by mass: 82.5 parts of fly ash, 17.5 parts of mineral powder, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0057] Comparative Example 2:

[0058] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that sodium silicate nonahydrate is removed and replaced with anhydrous sodium silicate.

[0059] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 13.5 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0060] Comparative Example 3:

[0061] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that anhydrous sodium silicate is removed and replaced with sodium silicate nonahydrate.

[0062] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 13.5 parts of sodium silicate nonahydrate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0063] Comparative Example 4:

[0064] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that the polypropylene fiber is removed.

[0065] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 2.0 parts of thixotropic agent and 42 parts of water.

[0066] Comparative Example 5:

[0067] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that an excess amount of polypropylene fibers is added.

[0068] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 1.50 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0069] Comparative Example 6:

[0070] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that the thixotropic agent is removed.

[0071] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 120 parts of quartz sand, 0.80 parts of polypropylene fiber and 42 parts of water.

[0072] Comparative Example 7:

[0073] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that the amount of quartz sand is reduced.

[0074] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 60 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0075] Comparative Example 8:

[0076] A solid waste-based high-toughness geopolymer for 3D printing is basically the same as Example 1, except that an excess amount of quartz sand is added.

[0077] The raw materials are respectively as follows in parts by mass: 80 parts of fly ash, 15 parts of mineral powder, 2.5 parts of light bentonite and 2.5 parts of light calcium carbonate, 9.5 parts of sodium silicate nonahydrate, 4.0 parts of anhydrous sodium silicate, 180 parts of quartz sand, 0.80 parts of polypropylene fiber, 2.0 parts of thixotropic agent and 42 parts of water.

[0078] Table 1 Comparison of the proportions of the embodiments and the comparative examples (unit: mass fraction)

[0079]

[0080] A method for preparing a solid waste-based high-toughness geopolymer for 3D printing, such as Figure 1 As shown, the specific steps are as follows:

[0081] (1) The polypropylene fiber was immersed in a 5.0% dispersant aqueous solution for 24 hours and then air-dried;

[0082] (2) the aluminosilicate precursor material, the composite solid activator, the thixotropic agent, the fine aggregate and the fiber are fully mixed and stirred for 20 minutes using a high-speed dry powder mixer to obtain a geopolymer composite dry mix;

[0083] (3) mixing the geopolymer composite dry mix and water in a concrete mixer for 10 minutes to obtain a geopolymer slurry with good fluidity and stacking properties;

[0084] (4) placing the geopolymer slurry in a printing bin of a frame-type concrete 3D printer, adjusting the extrusion rate and horizontal / vertical stepping speed of the printing nozzle according to a preset shape and printing path, thereby realizing a 3D printed geopolymer entity (or component) of a specific configuration;

[0085] (5) After printing, the 3D printed geopolymer entity needs to be sprayed with an appropriate amount of water on the outer surface every 4 hours (depending on the air humidity and ventilation conditions) using a spray bottle to maintain the humidity balance inside and outside the specimen to prevent shrinkage and cracking; 48 hours after printing, the 3D printed geopolymer entity has basic plastic strength and can be transferred to the curing room for curing to the standard curing age of 28 days.

[0086] The stackability index (Buildability index) and opening time (opening window) refer to the industry standards "Test Method for Basic Mechanical Properties of 3D Printed Concrete" (T / CBMF 183-2022 / T / CCPA 33-2022) and "Test Method for Performance of 3D Printed Concrete Mixtures" (T / CBMF 184-2022 / T / CCPA 34-2022).

[0087] A method for testing the stacking index of solid waste-based high-toughness geopolymers for 3D printing, specifically: using a 70mm diameter, 65mm height, and a total volume of 250cm 3 A cylindrical mould is prepared, and the freshly mixed geopolymer slurry (10 minutes after adding water) is freely injected into the mould three times without vibration to smooth the upper surface; the mould is slowly lifted up, and after the height of the cylindrical geopolymer slurry is stable, the residual height is measured four times at intervals of 90°, and the average value is taken. The ratio of the slump residual height of the geopolymer slurry to the initial height is the stacking index.

[0088] A method for testing the open time (open window) of solid waste-based high-toughness geopolymers for 3D printing, specifically: starting from the time of water addition, the maximum time for the geopolymer slurry to meet printability is measured every 5 minutes, that is, the time corresponding to the continuous and uninterrupted 3D printing geopolymer printing filament, in minutes.

[0089] A method for testing the anisotropic mechanical properties of solid waste-based high-toughness geopolymers for 3D printing, such as Figures 2 to 6As shown, specifically: after the 3D printed geopolymer entity was cured for 28 days, a desktop cutting machine was used to cut the sample along the printing direction (XY axis) and along the interlayer seam direction (YZ axis) to 150mm×45mm×45mm, and the compressive strength and flexural strength of the sample were measured.

[0090] Table 2 Comparison of printability of the embodiments and comparative examples

[0091]

[0092] Table 3 Comparison of anisotropic mechanical properties of examples

[0093]

[0094] In this embodiment, more than 90% of the aluminosilicate precursor material comes from solid waste, and a premixed geopolymer composite dry blend is used, which is easy to transport and store. At the same time, the 3D printed solid waste-based high-toughness geopolymer prepared based on the embodiment has the characteristics of stable printability and excellent mechanical properties. As shown in Table 2, the geopolymers of this embodiment all meet the 3D printable performance requirements, and the open time is more than 30 minutes, which can meet the needs of on-site construction. As shown in Table 3, the 3D printed solid waste-based high-toughness geopolymer has excellent flexural strength, and the flexural strength loss along the interlayer seam direction is within 15%.

[0095] Therefore, the 3D printed solid waste-based high-toughness geopolymer prepared based on the geopolymer composite dry mix listed in this embodiment has the characteristics of good printability, long development time, high strength, green environmental protection, low energy consumption, and low price, and is suitable for 3D printing high-toughness buildings.

[0096] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A solid waste-based high-toughness geopolymer for 3D printing, characterized in that: The components of the geopolymer are 100 parts of aluminosilicate precursor material, 13.5-16.5 parts of composite solid activator, 1.0-4.0 parts of thixotropic agent, 120-140 parts of fine aggregate, 0.60-1.20 parts of fiber and 36-44 parts of water in parts by weight. The aluminosilicate precursor material comprises fly ash, mineral powder, light bentonite and light calcium carbonate, wherein the components are 70-80 parts by mass of fly ash, 10-25 parts by mass of mineral powder, 2.0-5.0 parts by mass of light bentonite and 2.0-5.0 parts by mass of light calcium carbonate; The composite solid activator comprises anhydrous sodium silicate and sodium silicate nonahydrate, wherein the components are 2.5-5.0 parts of anhydrous sodium silicate and 8.5-12.0 parts of sodium silicate nonahydrate respectively in terms of mass fraction; The method for preparing the solid waste-based high-toughness geopolymer for 3D printing comprises the following steps: (1) Soaking the fiber in the dispersion; (2) mixing and stirring the aluminosilicate precursor material, the composite solid activator, the thixotropic agent, the fine aggregate and the fiber to obtain a geopolymer composite dry mix; (3) mixing and stirring the geopolymer composite dry mix and water to obtain a geopolymer slurry; (4) 3D printing the geopolymer slurry to obtain a 3D printed geopolymer entity; (5) 3D printed geopolymer entity maintenance.

2. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: The thixotropic agent is a nano-grade magnesium aluminum silicate plastic thickener.

3. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: The fine aggregate is prepared by mixing 20-40 mesh and 40-80 mesh quartz sand in a mass ratio of 1:(1-2).

4. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: The fiber is polypropylene fiber or polyvinyl alcohol fiber, with a length of 6.0-9.0 mm, a diameter of 18-48 μm, and a specific gravity of 0.91-0.

97.

5. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: In step (1), the solute of the dispersion is a ZY-DP type nanomaterial dispersant, and the solvent is water, 75% ethanol or anhydrous ethanol, with a mass fraction of 0.5-5.0%.

6. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: The soaking time in step (1) is 24-48 h.

7. The solid waste-based high-toughness geopolymer for 3D printing according to claim 1, characterized in that: The mixing and stirring time in step (2) is 10-20 min, and the mixing and stirring time in step (3) is 5-10 min.

Citation Information

Patent Citations

  • High-performance geopolymer concrete and preparation method thereof

    CN113998929A

  • Straw powder enhanced geopolymer for 3D printing of Zhaozhou Bridge and preparation method of straw powder enhanced geopolymer

    CN109437708A